Appropriate management of asymptomatic carotid stenosis. Issue 2 (27th April 2016) - Spence, J David; Song, Hongsong; Cheng, Guanliang
Abstract : With modern intensive medical therapy, the annual risk of ipsilateral stroke in patients with asymptomatic carotid stenosis (ACS) is now down to ∼0.5%. Despite this, there is a widespread practice of routine intervention in ACS with carotid endarterectomy (CEA) and stenting (CAS). This is being justified on the basis of much higher risks with medical therapy in trials conducted decades ago, compared with lower risks of intervention in recent trials with no medical arm. Such extrapolations are invalid. Although recent trials have shown that after subtracting periprocedural risks the outcomes with CEA and CAS are now comparable to medical therapy, the periprocedural risks still far outweigh the risks with medical therapy. In the asymptomatic carotid trial (ACT) 1 trial, the 30-day risk of stroke or death was 2.9% with CAS and 1.7% with CEA. In the CREST trial, the 30-day risk of stroke or death among asymptomatic patients was 2.5% for stenting and 1.4% for endarterectomy. Thus, intensive medical therapy is much safer than either CAS or CEA. The only patients with ACS who should receive intervention are those who can be identified as being at high risk. The best validated method is transcranial Doppler embolus detection. Other approaches in development for identifying vulnerable plaques include intraplaque haemorrhage on MRI, ulceration and plaque lucency on ultrasound, and plaque inflammation on positron emission tomography/CT. Intensive medical therapy for ACS includes smoking cessation, a Mediterranean diet, effective blood pressure control, antiplatelet therapy, intensive lipid-lowering therapy and treatment with B vitamins (with methylcobalamin instead of cyanocobalamin), particularly in patients with metabolic B12 deficiency. A new strategy called 'treating arteries instead of risk factors', based on measurement of carotid plaque volume, is promising but requires validation in randomised trials.